A Study on the Effectiveness of Dialogic Feedback in English Writing - Jin Zhang (Journal of Linguistics and Communication Studies, 2023)
Feedback in English writing plays an important role in promoting the development of students’ writing ability. As one of the feedback forms, dialogic feedback has been gradually integrated into the new teaching concept of EFL writing. This study investigates learners’ attitudes toward dialogic feedback compared with written feedback and passive oral feedback. The characteristics of dialogic interaction are observed. The effectiveness of dialogic feedback and the influence of learners’ second language ability and instructors’ noticing strategies on the quality of feedback are discussed. It especially covers the differences of learners’ focus on writing (content, organization, grammar and language) in the process of feedback. Based on the one-to-one peer feedback model of the English writing center of Nantong University, this study collects data from 65 undergraduates through feedback corpus, questionnaire survey and semi-structured interview. The results show that most learners have a positive attitude towards dialogic feedback, which can to a certain degree improve their L2 writing. The higher the learners’ L2 proficiency, the more effective the dialogic feedback is. It is also helpful to improve the quantity and quality of dialogic feedback that the tutor uses the appropriate noticing strategy. These findings not only confirm the effectiveness of dialogic feedback, but also help teachers to use dialogic feedback reasonably and improve the effectiveness of feedback in English writing class.